2016
DOI: 10.3389/fphys.2016.00213
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Hypoxanthine-Guanine Phosphoribosyl Transferase Activity in Bottlenose Dolphins Contributes to Avoiding Accumulation of Non-recyclable Purines

Abstract: Marine mammals are exposed to ischemia/reperfusion and hypoxia/reoxygenation during diving. During oxygen deprivation, adenosine triphosphate (ATP) breakdown implies purine metabolite accumulation, which in humans is associated with pathological conditions. Purine recycling in seals increases in response to prolonged fasting and ischemia. Concentrations of metabolites and activities of key enzymes in purine metabolism were examined in plasma and red blood cells from bottlenose dolphins (Tursiops truncatus) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Intriguingly, we observed that the levels of some nucleotides and organic acids were significantly increased (e.g., hypoxanthine), whereas the levels of some nucleotides and organic acids were significantly reduced [e.g., guanosine monophosphate (GMP)]. Hypoxanthine-guanine phosphoribosyl transferase (HPRT) is an important enzyme involved in nucleotide recycle pathway and can covert hypoxanthine and guanine to inosine 5’-monophosphate (IMP) and GMP, respectively (12, 13). The observed abnormal levels of hypoxanthine and GMP suggested that the function of HPRT had become defective in these COVID-19 fatal patients, which could result in the disorders of purine and pyrimidine metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, we observed that the levels of some nucleotides and organic acids were significantly increased (e.g., hypoxanthine), whereas the levels of some nucleotides and organic acids were significantly reduced [e.g., guanosine monophosphate (GMP)]. Hypoxanthine-guanine phosphoribosyl transferase (HPRT) is an important enzyme involved in nucleotide recycle pathway and can covert hypoxanthine and guanine to inosine 5’-monophosphate (IMP) and GMP, respectively (12, 13). The observed abnormal levels of hypoxanthine and GMP suggested that the function of HPRT had become defective in these COVID-19 fatal patients, which could result in the disorders of purine and pyrimidine metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…This ATP is quickly catabolized to adenosine then to hypoxanthine creating a milieu similar to that described above for moderate hypoxia [30]. Elevated levels of hypoxanthine may consequently trigger upregulation of XOR activity in addition to activating purine salvage via hypoxanthine-guanine phosphoribosyltransferase (HPGRT) [33]. Interestingly, we have previously described upregulation of XOR via adenosine activation of adenosine A 2B receptors on endothelial cells [24].…”
Section: Xor Regulationmentioning
confidence: 87%
“… 76 The apparent disconnect between the present findings and the literature is reconciled by the observation that hypoxanthine levels in mitochondria-free RBC are not necessarily related to plasma levels of this metabolite (especially in the platelet and white blood cell-filtered environment of a packed RBC unit); for example, this is observed in underwater mammals, such as dolphins, which are constantly exposed to prolonged periods of hypoxia. 77 Thus, hypoxanthine levels in isolated RBC (as in stored RBC units), or in circulating RBC after exposure to high altitude, may not directly correlate with plasma hypoxanthine levels.…”
Section: Discussionmentioning
confidence: 99%